Indian English and the Fiction of National Literature / [electronic resource] - George, Rosemary Marangoly (Cambridge : Cambridge University Press, 2013)
During the twentieth century, at the height of the independence movement and after, Indian literary writing in English was entrusted with the task of consolidating the image of a unified, seemingly caste-free, modernising India for consumption both at home and abroad. This led to a critical insistence on the proximity of the national and the literary, which in turn, led to the canonisation of certain writers and themes and the dismissal of others. Examining English anthologies of 'Indian literature', as well as the establishment of the Sahitya Akademi (the national academy of letters) and the work of R. K. Narayan and Mulk Raj Anand among others, Rosemary George exposes the painstaking efforts that went into the elaboration of a 'national literature' in English for independent India even while deliberating the fundamental limitations of using a nation-centric critical framework for reading literary works.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: National characteristics, East Indian, in literature; Group identity in literature